2017
DOI: 10.3201/eid2302.161026
|View full text |Cite
|
Sign up to set email alerts
|

Diphyllobothrium nihonkaiense Tapeworm Larvae in Salmon from North America

Abstract: Diphyllobothriosis is reemerging because of global importation and increased popularity of eating raw fish. We detected Diphyllobothrium nihonkaiense plerocercoids in the musculature of wild pink salmon (Oncorhynchus gorbuscha) from Alaska, USA. Therefore, salmon from the American and Asian Pacific coasts and elsewhere pose potential dangers for persons who eat these fish raw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Outbreaks are generally associated with raw salmon products, like sushi, sashimi or carpaccio (EFSA, 2010e; Løvdal, 2015). D. nihonkaiense tapeworm larvae, previously only found in North East Asia, was recently detected for the first time in wild pink salmon from Alaska, US by (Kuchta et al, 2017). They indicated that this parasite might be a re-emerging issue due to "global importation and increased popularity of eating raw fish".…”
Section: Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks are generally associated with raw salmon products, like sushi, sashimi or carpaccio (EFSA, 2010e; Løvdal, 2015). D. nihonkaiense tapeworm larvae, previously only found in North East Asia, was recently detected for the first time in wild pink salmon from Alaska, US by (Kuchta et al, 2017). They indicated that this parasite might be a re-emerging issue due to "global importation and increased popularity of eating raw fish".…”
Section: Farmingmentioning
confidence: 99%
“…Farming Emerging parasites from wild salmon that are transferred to farmed salmon. 1,2 (Beldsoe and Oria, 2001;Hastein et al, 2006;Marty, 2008;Skov et al, 2009;EFSA, 2010e;Løvdal, 2015;Kuchta et al, 2017 Disclaimer: The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Humanmentioning
confidence: 99%
“…The first intermediate host (species in which the procercoid develops) is probably brackish zooplanktonic copepods ( 7 ). The first intermediate host is consumed by the second intermediate host, Pacific salmonids, namely cherry salmon ( Oncorhynchus masou ), chum salmon ( O. keta ), and pink salmon ( O. gorbuscha ) ( 8 10 ). In the second intermediate host, procercoids develop into plerocercoids, the larval form needed to infect the definitive host (e.g., humans).…”
mentioning
confidence: 99%
“…At 3 months follow-up, repeat stool examinations were negative. D. nihonkaiense is the second most common causative agent of diphyllobothriosis in humans 1. Adult tapeworms can achieve a length of more than 10 m in the small intestine.…”
mentioning
confidence: 99%
“…Most cases have been reported from Japan and also reported in Taiwan, China, Russia, France, Switzerland and New Zealand 2 3. Additionally, D nihonkaiense was found in the musculature of wild pink salmon in North America in 20131. Freezing fish at −20°C for at least 24 hours or −35°C for 15 hours or cooking fish at 55°C for more than 5 min is sufficient to kill Diphyllobothrium larvae in fresh fish to prevent parasitic infection.…”
mentioning
confidence: 99%